Endonuclease G promotes preeclampsia by regulating the Wnt signaling pathway - Jing Yang; Xuejun Kou (Taylor & Francis Group, 2023)
This study was conducted to investigate the effect and underlying mechanism of endonuclease G (ENDOG) on preeclampsia (PE). Differentially expressed genes in four Gene Expression Omnibus datasets (GSE147776, GSE96984, GSE102897, and GSE65271) were identified using a Venn diagram. Normal and PE placental tissues were collected from normal and PE parturients. The expression of ENDOG in tissues was tested using western blotting, quantitative reverse transcription-polymerase chain reaction, and immunohistochemistry. Cell viability, proliferation, invasion, and migration were detected using Cell Counting Kit-8, 5-ethynyl-2'-deoxyuridine, transwell, and wound healing assays, respectively. Angiogenesis was detected using tube formation and enzyme-linked immunosorbent assays. Kyoto Encyclopedia of Genes and Genomes analysis was performed to analyze the downstream mechanisms of ENDOG in PE. Wnt pathway-related protein levels were detected using western blotting. ENDOG was highly expressed in preeclampsia tissues and HTR-8/SVneo cells. Overexpression of ENDOG inhibited HTR-8/SVneo cell growth, proliferation, invasion, migration, and angiogenesis. Moreover, the levels of angiopoietin-1 and pathway-related proteins were markedly decreased by ENDOG upregulation. Knockdown of ENDOG had the opposite effects, which were counteracted by the inhibitor of Wnt production-2. ENDOG expression was upregulated in preeclampsia and affected HTR-8/SVneo cell proliferation, invasion, migration, apoptosis, and angiogenesis via the Wnt signaling pathway. This provided a novel strategy for the prevention and treatment of PE.